In Vitro Investigation of the Effect of Silanizing on the Microshear Repaired Bond Strength of Short-Fiber Composites after Surface Treatment with an Er;Cr:YSGG Laser, Sandblasting, or Bur - Zakavi, Faramarz; Mohamadi, Nasrin; Kaviani, Azita (Galen Medical Journal, 2024)
Background: This study aimed to evaluate the effect of various interfacial surface treatments on the repair micro shear bond strength (μSBS) of aged short fiber-reinforced composite (SFRC). Methods and Materials: The substrate and repair composite material used in the fabrication of eighty samples were SFRC (Ever-X posterior, GC). Based on the mechanical roughening method, the samples were divided into four categories: diamond bur, sandblasting, laser treatment, and a control group. Then, they were split into two groups using the chemical conditioning method: those using a universal glue that contains silane and those using a separate silane step before the universal adhesive that contains silane. After 40 days of immersion in distilled water at 37°C, the specimens were removed. Universal testing equipment was used to implement SBS testing. Using field emission scanning electron microscopy (FESEM), the surface topography of the composite material was examined after the roughening procedures. Results: Although the laser group had the highest μSBS value, there was no statistically significant difference in μSBS across the groups (P > 0.05). The results for μSBS were also not significantly different when using universal adhesive with or without an extra silanizing step (P > 0.05). Conclusion: Based on the results, the other groups’ μSBS values were lower than those of the laser group. Incorporating a distinct silanization process before applying the universal adhesive that contained silane did not improve the μSBS either.